ANALYSIS OF THE IMPLEMENTATION OF REST HOURS MANAGEMENT FOR THE CREW OF THE KM. MUTIARA FERINDO VII IN ACCORDANCE WITH THE MARITIME LABOR CONVENTION - Wahyu Anugrah Tahir; Bruce Rumangkang; Nurul Hatifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of Rest Hours Management for the crew of KM Mutiara Ferindo VII in accordance with the Maritime Labour Convention (MLC) 2006. Rest Hours Management is a key aspect of ensuring seafarers’ welfare while also maintaining operational safety in shipping. research used a descriptive qualitative approach data collected through in-depth interviews, direct observation during 12 months of sea practice, and literature review. results indicate, normatively, application Rest Hours Management refers provisions Maritime Labour Convention (MLC) 2006. However, its implementation aboard KM Mutiara Ferindo VII has not been optimal. caused by individual crew behavior that affects the effectiveness of implementation; some crew members do not make optimal use of rest periods and instead use them for recreational activities (sightseeing). This situation leads to suboptimal rest, which in turn reduces physical condition and work performance and increases risks to health and safety. Thus, the implementation of Rest Hours Management on the vessel has not yet reached the expected level of efficiency.